2012
DOI: 10.1007/s00221-012-3325-z
|View full text |Cite
|
Sign up to set email alerts
|

Hand use for grasping in a bimanual task: evidence for different roles?

Abstract: It has been proposed that the two hands play different roles during bimanual object interaction. The right hand takes on an explorative, highly precise, manipulative role while the left hand supports and stabilizes the object. Does this division of labour influence hand use during visually guided grasping? Three experiments were designed to address this question: right-handed individuals put together 3D models using big or small building blocks scattered across a tabletop. Participants were free to build the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
63
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(72 citation statements)
references
References 41 publications
9
63
0
Order By: Relevance
“…Although our sample size is comparable to many of the other hand choice studies reviewed above, the recent extensions of the Gonzalez puzzle/model paradigm using a distinct sample of left handers (Gonzalez & Goodale, 2009;Stone et al, 2013) suggests that using their paradigm the effects are reliably obtained.…”
Section: Discussionmentioning
confidence: 83%
“…Although our sample size is comparable to many of the other hand choice studies reviewed above, the recent extensions of the Gonzalez puzzle/model paradigm using a distinct sample of left handers (Gonzalez & Goodale, 2009;Stone et al, 2013) suggests that using their paradigm the effects are reliably obtained.…”
Section: Discussionmentioning
confidence: 83%
“…Tests of normality (Kolmogorov-Smirnov & ShapiroWilk) revealed that the data was normally distributed. An analysis of variance (ANOVA) was performed on the values of right-hand use, as in previous reports using similar tasks and measures (Bryden & Huszczynski, 2011;Bryden, Pryde & Roy, 2000;Cavill & Bryden, 2003;de Bruin, Bryant & Gonzalez, 2014;Sacrey, Arnold, Whishaw & Gonzalez, 2013;Stone & Gonzalez, 2014a,b;Stone et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Not surprisingly, vision also plays a critical role in hand preference for grasping. During visually-guided grasping tasks, individuals (even some left-handed) exhibit a clear preference to grasp objects with the right-hand (Bishop, Ross, Daniels & Bright, 1996;Calvert & Bishop, 1998;Gabbard & Rabb, 2000;Gonzalez & Goodale, 2009;Jacquet, Esseily, Rider & Fagard, 2012;Stone & Gonzalez, 2014a;Stone, Bryant & Gonzalez, 2013). The role of haptics in hand preference for grasping however, has been seldom investigated.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations